Simulation of Flare Discharged from Oil Fields, Integration of Remote Sensing, Laboratory and Mathematical Models - Ali, Jafar A.; Khodakarami, Loghman; Ali, Brosk F. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
The prevailing practice in Iraq and the Middle East involves the flaring of gas into the atmosphere by a majority of oil and gas industries. This practice, however, is causing significant harm to the environment, personnel, and equipment. Consequently, determining the optimal location for the flare stack within an oil field has become a primary concern in the design of oil field processes. To address this issue, an in-depth analysis of the flame distribution from oil field flare stacks has been undertaken, focusing on assessing both the size and configuration of the flare. The investigation specifically concentrated on the diffusion of the heat around a flare discharged from a vertically positioned cylindrical pipe into the atmosphere. To facilitate this exploration, a geographic information system was used, and an environmental laboratory experiment was conducted using a scaled flare stack, allowing for measurements under various conditions. During this experiment, thermal images of the flare at different gas flow rates were captured and analyzed using MATLAB software to precisely measure the dimensions and shape of the flare. Consequently, predicting the shape and size of flare profiles becomes possible when key parameters, such as discharge gas flow rate, are known. The overarching objectives of this study are to forecast the shape and size of the flare as well as the diffusion zone, contributing to a more effective and environmentally friendly oil field process design.